Social Context on an Agreement Letter of Sri Sultan Paduka Guvernement of Hindia Nederland and the Kingdom of Bima - Diansyah, Nurrahman (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2016)
The release of a treaty between Sri Sultan Paduka Guvernement successor agreement Hindia Netherlands and the Kingdom of Bima is a relationship product. It means that a text of the letter agreement cannot be separated from the social context of the time. The theory of the social context LFS Hallidayan is adopted in a social context study. Data, collected through the literature and interview methods, are analysed through the procedure of analyzing qualitative data instituted by Milles and Huberman (2014). The finding shows that a written agreement was made in institutionalized situation in the kingdom of Bima involving both the Government of the Hindia Netherlands and the Kingdom of Bima. Bima Kingdom became the imperior wrapper while the Hindia Netherlands government became the superior wrapper. The treaty governs the rights and obligations of both parties. This is written with regard to gender ekplanasi of ideological hegemony, which includes the .Hindia Netherlands against Bima Kingdom through the regulation of rights and obligations.